Espaço-imagético religioso: experiências marianas das novas comunidades católicas Maranata e Rainha da Paz da diocese de Sobral (CE) - Moraes, Antonio Jarbas Barros de (2023)
The study is based on the investigative contribution of Cultural Geography, especially in the Geography of Religion subfield. In this regard, there are countless paths of understanding within the scope of devotional religiosity that affect space. Therefore, the objective of the research was to understand the New Catholic Communities Maranata and Rainha da Paz from the spatial implications of the Mariana´s faith or Marianismo linked to the diocese of Sobral, in the Brazilian state of Ceará, including its diffusing/radiating power that influences and receives (inter)national influence. The methodology used research on theoretical references, gathering documents from communities, the diocese, websites and social networks, fieldwork with visits-observations-participation, notes, drafts and scribbles in the field notebook, using semi-structured interviews and a form disseminated on social networks, based on these materials, databases were assembled or the source memorial for doing research, thematic maps and cognitive mapping that guided the reading-writing process. It resulted, from a phenomenological point of view, in a cultural approach to Geography within the scope of the meanings of the communita-liminal place, involving meanings of Marian religious experiences, political tensions, conservatisms, contradictions and ambiguities. It is about the geographic dynamics, activated by the Marian devotional experience, giving rise to the notion of Espaço-imagético Religioso (EIR). In addition to the segmented context, the geography of communities exists continuously due to the practical and symbolic dimension of the religious phenomenon.